Architecture of the administrative centre of Kharkiv, the capital – laboratory for the creation of the New Man: from concept to implementation - Kateryna Didenko; Olena Gella (Budownictwo i Architektura, 2024)
The interest in addressing social and political problems through architecture entered the professional discourse of Ukrainian architects in the 1920s. The creation of a new Soviet man became one of the central ideas of the early Soviet state. As a result of the planned transformation of social and family life, there was an active search for new typologies and concepts in both residential and public architecture. The creation of "social condensers," as a means of spatially materializing the idea of shaping a new Soviet man through architecture, became one of the most significant leitmotifs in the formation of architectural and urban planning ensembles in the capital city of Kharkiv, Kharkiv is known not only as a site for creating world renowned modernist complexes, but also as a venue for implementing social experiments. This article explores an example of such a "social condenser" through the ensemble of the Dzerzhynskyj Square (now Svobody Square) district, featuring its unique residential block-combines, as well as architectural concepts that were not realized in their originally conceived form.